Preparação, caracterização e avaliação biológica de arcabouços 3D de alginato, fibroína e hidroxiapatita para regeneração tecidual óssea - Carvalho, Geane Conceição (2018)
Recent researches in bioengineering allow the production of three-dimensional biodegradable scaffolds to act as temporary support in bone tissue regeneration. In this perspective, the in vitro behavior of porous 3D scaffolds based on sodium alginate (SA), silk fibroin (SF) and hydroxyapatite (HA) at different proportions was evaluated as follows: group I: SA (100 wt.%), group II: SA/SF/HA (25:25:50 wt.%), group III: SA/SF/HA (50:25:25 wt.%), group IV: SA/SF/HA (35:35:30 wt.%), face to MC3T3-E1 and MG-63 cells, for a possible application in bone tissue engineering. Physical-chemical analyzes were performed using Fourier transform infrared spectroscopy and X ray diffraction, in order to demonstrate the physical interaction of the materials in the composite. In addition, the thermal degradation behavior of the scaffolds was assessed by thermogravimetric analysis and differential scanning calorimetry which provided an understanding of possible thermal events. Morphological changes and microstructure analyzes were observed in a bioactivity assay and by computerized microtomography, respectively. Finally, we conclude that regardless of composition, all the scaffolds produced have a topography and microstructure composition capable of promoting osteogenic adhesion, proliferation and differentiation, more effectively, as verified by biological assays. However, the frameworks were considered biocompatible and therefore feasible for use as supports in the regeneration of bone tissue.